Language and communicative practices - William F Hanks (Westview, 1996)
The book is divided into three parts: The first, entitled "Language the System", explores classic grammatical and semiotic theories. The second part, "Language the Nexus of Context", examinesthe idea of context, starting from linguistic pragmatics and moving on to phenomenology. The third and final part of the book, "Comminicative Practices", proposes a synthesis in three steps: The basic elements of communicative practice, corporeality in language, and meaning in history